PENGARUH INVIGORASI TERHADAP VIABILITAS BENIII DAN PERTUMBUHAN TANAMAN KENAF (Hibiscus cannabinus L.) - HARTATl, RR. SRI; SUDJINDRO, SUDJINDRO; INDRIANI, FEBRIA CAHYA (Jurnal Penelitian Tanaman Industri, 1999)
Effect of invigoration on seed viability and plant growth of kenaf (Hibiscus cannabinus I.)I aw vigour and viability of seed is the main factor causing the low productivity of crops. One of the methods of improving a deteriorating seed is in vigoratioo. The study was aimed at evaluating the effect of invigwation treatment on seed viability, plant growth and yield of kenaf (Hibiscus cannabinus). The experiment was conducted in two steps. The irst step was conducted in the laboratory of the Research Institute for Tobacco and Fibre Crops. Malang from Januai to April 1998 and the second step was conducted at Asembagus Expeimental Farm from Januai to May 1998. The experiment in the laboratory was designed as a completely randomized design while the field expeiment was done as a randomized block. The treatments were arranged factoially The irst factor was the seed vigour (growth uniformity) i.e. 40 or 60%, and the second factor was tnvigoration treatment, i.e control (untreated), water, sodium phosphate (2x10 M), sodium thiosulphatc ( 2 x 10 M), or tannic acid (2 x 10"* M). Results showed that invigoration treatments were not effective, when they were applied on the seed of 40% vigour. On the seed of 60% vigour, the invigoration improved seed vigor and viability. Treating the seed of 60% vigour with sodium phosphate (2x10 M) improved growth uniformity by 20% and potential viability by 7%, while applying the seed with sodium thiosulphnte decreased elcctroconductivity by 24.59 Mmhos/g compared to the control. Furthermore, treating seed of 60% vigour with sodium phosphite improved plant stand by 7 33%. increased plant height by 19 an. stem diameter bv 2 cm and fresh stem per plot (9at ) by 633 kg.